2018
DOI: 10.3390/cells7090131
|View full text |Cite
|
Sign up to set email alerts
|

PDGFR and IGF-1R Inhibitors Induce a G2/M Arrest and Subsequent Cell Death in Human Glioblastoma Cell Lines

Abstract: Glioblastomas are highly resistant to radiation and chemotherapy. Currently, there are no effective therapies for this type of tumor. Signaling mechanisms initiated by PDGFR and IGF-1R are important in glioblastoma, and inhibition of the signal transduction pathways initiated by these receptors could be a useful alternative strategy for glioblastoma treatment. We have studied the effects of the PDGFR inhibitor JNJ-10198409 (JNJ) and the IGF-1R inhibitor picropodophyllin (PPP) in glioblastoma cell lines as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 52 publications
0
22
0
Order By: Relevance
“…Both, free and immobilized, CLytA-DAAO chimera are able to induce cell death by increasing ROS production, which caused DNA damage in several colon carcinoma and pancreatic adenocarcinoma cell lines as well as in glioblastoma cell lines derived from primary cultures obtained in our laboratory directly from glioblastoma patients, at doses that are safe for non-tumor cells. Interestingly, the cell death evoked by the enzyme could be executed by apoptotic or necrotic mechanisms depending on the tumor origin.The reasons to select these types of tumors in our study were their frequency, mortality, and resistance to other treatments and also our laboratory experience, since we have been working in these models for many years [19][20][21][22][23]. This localized therapy reduces the dose of drug needed, improving the effectiveness and decreasing adverse effects.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Both, free and immobilized, CLytA-DAAO chimera are able to induce cell death by increasing ROS production, which caused DNA damage in several colon carcinoma and pancreatic adenocarcinoma cell lines as well as in glioblastoma cell lines derived from primary cultures obtained in our laboratory directly from glioblastoma patients, at doses that are safe for non-tumor cells. Interestingly, the cell death evoked by the enzyme could be executed by apoptotic or necrotic mechanisms depending on the tumor origin.The reasons to select these types of tumors in our study were their frequency, mortality, and resistance to other treatments and also our laboratory experience, since we have been working in these models for many years [19][20][21][22][23]. This localized therapy reduces the dose of drug needed, improving the effectiveness and decreasing adverse effects.…”
mentioning
confidence: 99%
“…The reasons to select these types of tumors in our study were their frequency, mortality, and resistance to other treatments and also our laboratory experience, since we have been working in these models for many years [19][20][21][22][23]. This localized therapy reduces the dose of drug needed, improving the effectiveness and decreasing adverse effects.…”
mentioning
confidence: 99%
“…The critical role that the IGF axis plays in the growth of GBM has been well documented in various experimental models ( 6 , 22 , 23 ). In early studies, the IGFs were shown to enhance 3D growth of glioblastoma ( 21 ) and more recently, high IGF-IR expression levels were identified as an independent prognostic factor associated with shorter survival, a poorer response to temozolomide ( 4 ) and resistance to anti-EGFR ( 24 ) and anti-PDGFR ( 25 ) treatments in GBM patients.…”
Section: Discussionmentioning
confidence: 99%
“…In many human malignancies, including GBM, upregulated expression of IGF-IR, IGF-I, IGF-II or combinations thereof have been documented (2,4). Therefore, targeting the IGF system, by inhibiting ligand or receptor synthesis and/or function could provide effective therapeutic approaches to the treatment of GBM (5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, ZNF24 may contribute to cell cycle promotion and maintenance of the progenitor stage of neural cells (41). Platelet-derived growth factor receptor (PDGFR) signaling is a crucial mechanism for the initiation and development of GBM (42). In GBM cell lines, ZNF24 negatively regulates two transcription factors, vascular endothelial growth factor (VEGF) and PDGFR-β (43).…”
Section: Discussionmentioning
confidence: 99%